Biological and physico-chemical mechanisms accelerating the acclimation of Mn-removing biofilters. (1st December 2021) - McCormick, N.E.; Earle, M.; Ha, C.; Hakes, L.; Evans, A.; Anderson, L.; Stoddart, A.K.; Langille, M.G.I.; Gagnon, G.A.
Highlights: Investigation of mechanisms for Mn oxidation in new GAC and anthracite biofilters. An acclimated Mn oxidizing microbiome formed in GAC and anthracite biofilters. Treatment and adsorption accelerated homogeneous Mn oxidation in GAC. Treatment delayed formation of a Mn oxidizing microbiome in anthracite. Abstract: This study investigated treatment strategies which accelerated the acclimation of new Mn-removing biofilters to help utilities respond to changing Mn regulations, such as the recent introduction of a health-based maximum acceptable concentration and a reduction in the aesthetic objective for Mn in drinking water by Health Canada. Bench-scale filters of either GAC or anthracite media were fed with applied water containing Mn (17–61 μg/L) from a full-scale plant over 294 days. Treatment strategies included the addition of H2 O2 (1 mg/L) and/or an increase in pH from 6.8 to 7.5 through the addition of NaOH. The potential physico-chemical and biological mechanisms responsible for accelerated biofilter acclimation under the various redox conditions were investigated through thermodynamic modelling, to predict homogeneous Mn oxide formation, and 16S rRNA gene amplicon sequencing, to characterize the microbial community within the filters. GAC filters treated with NaOH, and both H2 O2 and NaOH, were the first to acclimate (< 20 μg/L Mn in filter effluent) after 59 and 63 days respectively, while the ambient GAC filter took almost 3 times as long to acclimate (168 days), and the anthracite filters which received the same chemically adjusted water took almost 4 times as long (226 and 251 days, respectively). The accelerated acclimation in the treated GAC filters was likely due to physico-chemical oxidation via three potential mechanisms: (1) homogeneous oxidation of dissolved Mn(II) to Mn(III)/Mn(IV) oxides and the subsequent removal of oxides from solution through adherence to the GAC surface, (2) adsorption of dissolved Mn(II) to GAC and subsequent homogeneous or biological oxidation, or (3) formation of colloidal Mn(III)/Mn(IV) oxides and subsequent adsorption of dissolved Mn(II) to the Mn colloids. In the untreated GAC filter and all anthracite filters, which did not benefit from improved redox conditions or an active surface, physico-chemical mechanisms alone were insufficient for consistent Mn removal to less than 20 μg/L. Acclimation in these filters was delayed until a microbiome enriched with bacteria capable of biological nitrification and Mn oxidation evolved within the filters. The acclimated microbiome was consistent between GAC and anthracite filters and was significantly different from the non-acclimated microbiome ( p < 0.001) initially formed during the early operation of the filters. Interestingly, treatment with NaOH, and NaOH and H2 O2, which accelerated physico-chemical oxidation in GAC filters, was observed to delay the development of biological oxidation in anthracite filters, and thus deferred acclimation. Although some filters took longer to acclimate than others, once acclimation was reached all filters had a similar microbiome and were able to consistently remove Mn to below 20 µg/L. Graphical abstract: Image, graphical abstract